Metabolic compromise in women with PCOS: earlier than expected - Lana,Maria Perez (2020)
SUMMARY Polycystic ovary syndrome (PCOS) is an endocrinopathy with unknown pathophysiology among women of reproductive age. Several studies have been conducted to determine the prevalence of metabolic syndrome (MetS) among PCOS patients. Recent studies have reported varied prevalence of metabolic syndrome (MetS) in women with PCOS. The aim of this study is to determine if women with PCOS are at a higher risk of MetS or some degree of metabolic compromise. METHODS: This is an observational study. A total of 96 women diagnosed with PCOS (according to the Rotterdam consensus criteria) were included. Variables of diagnostic criteria for MetS according to the ATP III were analyzed at the first consultation. Data analysis was performed using Epi Info™ 7.2.2.16. RESULTS: We assessed the prevalence of obesity, blood pressure, glucose intolerance, and dyslipidemia in 96 women with PCOS and an average age of 28 (17-39) years. Forty percent of the women had BMI <25 kg/m2; 85.4% had blood pressure <130/85 mm Hg; 22.9% had HDL cholesterol >50 mg/dl, 57.3% had triglycerides <150 mg/dl, 63.5% had fasting glucose <100 mg/dl. According to the ATP III criteria for MetS, 8.33% met none of the criteria, 19.79% met one criterion, 15.63% two criteria, 41.67% 3 criteria, 13.54% 4 criteria, and 1.04% met the 5 criteria. CONCLUSION: Considering the high prevalence of MetS or altered metabolic components in PCOS patients at the moment of the diagnosis, its regular screening is necessary to reduce the mortality and morbidity rates in these women.